Correction to: Determinants of the quality of care relationships in long-term care - a systematic review - Aukelien Scheffelaar; Nanne Bos; Michelle Hendriks; Sandra van Dulmen; Katrien Luijkx (BMC, 2019)
In the original publication of this article [1], there is a layout mistake in the column "McCloughen et al. (2011)" of Table 2.